Parasocial Interactions in Online Fan Applications (Qualitative Study on Nctzen use of the LYSN application) - Muthaharah, Anisa Siti; Kusuma, Rina Sari (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
The phenomenon of fanaticism towards the K-pop industry is increasingly widespread and easy to find. Compared to a few years ago when interacting with celebrities could only be mediated by sending letters at press conferences or opportunities to meet their idols. Now with online social media making it easier for fans to interact with their idols all over the world, this can lead to parasocial relationships being established. One platform that connects fans and their idols is the fandom application, namely the Lysn DearU Bubble application which is the focus of this research. This research also aims to determine the formation of parasocial relationships in a paid service application called LYSN DearU Bubble. With data analysis techniques in this research using in-depth interviews and documentation with fans who have Bubble accounts with a type of virtual ethnographic data collection. By using the attraction-addiction theory, this research shows that fans who subscribe to the LYSN fandom application tend to feel closer to their idols compared to fans who do not subscribe to LYSN, the content presented by the artist is what makes this application special and still used by fans even though this application is paid.